Who should participate in health care priority setting and how should priorities be set?: Evidence from a Portuguese survey - Veloso,Anabela Botelho (2013)
Introduction This article provides highlights of the evolution of the health care rationing debate towards a more explicit and open approach involving public participation. Discretionary models that have dominated the health sector decision-making are being questioned by different sectors of society. Methods Using data from 442 college students, we explore public views on public involvement in health care rationing decisions. Results Findings suggest that although citizens wish to be consulted, they believe doctors should play the most important role on rationing decisions. Discussion Confidence in doctors is, nonetheless, not independent from the criteria used to support their decisions.